2022
DOI: 10.1021/acs.energyfuels.2c03518
|View full text |Cite
|
Sign up to set email alerts
|

Ball-Milling-Triggered Synthesis of Si/C/SiC@MCMB Composites from Carbon Dioxide for Improved Lithium Storage Capability

Abstract: The excessive emission of carbon dioxide (CO2) poses a serious threat to the sustainable development of human beings. The efficient conversion of CO2 into high-value-added chemicals is of great significance for solving the greenhouse effect and energy crisis. Herein, a new strategy is proposed to turn CO2 into Si/C/SiC composites through a one-step ball-milling reaction with Mg2Si at room temperature. Moreover, mesophase carbon microspheres (MCMB) are introduced into reactants to prepare Si/C/SiC@MCMB composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The value of I D /I G indicates the degree of graphitization. 33 The value of I D /I G for the three Si/C/CNFs composites is about 0.93, demonstrating a similar graphitization degree. Figure S6a exhibits the Raman spectra of the Si/C and Ni-Si/C composites, which has similar results to Figure 5a.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The value of I D /I G indicates the degree of graphitization. 33 The value of I D /I G for the three Si/C/CNFs composites is about 0.93, demonstrating a similar graphitization degree. Figure S6a exhibits the Raman spectra of the Si/C and Ni-Si/C composites, which has similar results to Figure 5a.…”
Section: Resultsmentioning
confidence: 79%
“…The two peaks at 514 and 955 cm –1 correspond to crystalline Si, and another two peaks located at 1345 and 1598 cm –1 are attributed to the D and G bands of carbon. The value of I D / I G indicates the degree of graphitization . The value of I D / I G for the three Si/C/CNFs composites is about 0.93, demonstrating a similar graphitization degree.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable efforts have been made to tackle these issues of the Si-based anode before the full implementation in LIBs. Combining Si with conducting and buffering components is confirmed to be an effective strategy . Carbon nanotubes (CNTs) are characterized by high electrical conductivity and high mechanical strength; therefore, the conductive network constructed by CNTs can improve the electrical conductivity of Si-based materials and provide a buffer component for the volume expansion. For example, Wei et al combined porous Si, graphene oxide, and CNTs by a rapid freeze-drying and heating treatment method.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that the above defects can be mitigated by combining Si with various carbon materials. Obviously, the uniform dispersion and good interface contact of Si and C components are the key issues to achieving high electrochemical performance. To date, a ball-milling method is mostly used for industrial production of a Si/C composite due to its simple operation, high material utilization, and low cost. However, it still suffers from weak interface bonding and poor interfacial contact of Si and C by the conventional ball-milling process. Therefore, it is highly necessary to find a new ball-milling strategy to modify the combination of Si and C components.…”
Section: Introductionmentioning
confidence: 99%